ANALISIS PENYERTAAN AGUNAN DALAM PEMBIAYAAN MUDARABAH: : Perspektif Fatwa DSN-MUI No. 07/DSN-MUI/IV/2000 dan Undang-Undang No. 21 Tahun 2008 tentang Perbankan Syari’ah - Muhammad Saifi (LP3M IAI Al-Qolam, 2021)
Islamic banking offers various types of sharia-based financing. One of them is mudarabah financing agreement based on profit sharing, in which the bank requires collateral (guarantee) as well as credit application in conventional banking. In classical fiqh literature, the true mudarabah contract is not allowed to include collateral. However, the bank has its own reasons for implementing it and running its business in accordance with statutory regulations and other supporting instruments such as the DSN-MUI Fatwa. This research is qualitative normative research with conceptual and law official regulation approach. The law materials in this research includes the primary, secondary, and tertiary law material. Primary law material is obtained from the official regulations concerning with the collateral in defrayal of Syari’ah bank and Fatwa DSN-MUI about mudarabah defrayal. Secondary law material is obtained from the books related to the collateral and mudarabah. The tertiary law material is obtained from law dictionary and encyclopedia containing the collateral and mudarabah. This research concluded that Islamic bank could determine the collateral as the requirement in mudarabah defrayal based on accurate principle of the bank and avoid deceitfulness of client. The law No. 21 of 2008 about Syari’ah banking, 26 article 1, clearly stated that the collateral is determined in paying client obligation to the Syari’ah bank. In Fatwa DSN-MUI No. 07/DSN-MUI/IV/2000, the collateral is determined to avoid the divergence committed by mudl?rib.